Using Genetic Code Expansion for Protein Biochemical Studies - Chung, Christina Z.; Amikura, Kazuaki; Söll, Dieter (Frontiers in Bioengineering and Biotechnology, 2020)
Protein identification has gone beyond simply using protein/peptide tags and labeling canonical amino acids. Genetic code expansion has allowed residue- or site-specific incorporation of non-canonical amino acids into proteins. By taking advantage of the unique properties of non-canonical amino acids, we can identify spatiotemporal-specific protein states within living cells. Insertion of more than one non-canonical amino acid allows for selective labeling that can aid in the identification of weak or transient protein–protein interactions. This review will discuss recent studies applying genetic code expansion for protein labeling and identifying protein–protein interactions and offer considerations for future work in expanding genetic code expansion methods.